Implementation of Problem Based Learning Assisted with Science Comic Books to Improve Critical Thinking Skill of Elementary Students (Universitas Negeri Semarang, 2020)
This research aims to improve students’ critical thinking skill using Problem Based Learning assisted science comic book media. This is a Classroom Action Research (CAR) with 2 cycles. The research subjects were 29 students in VB class of State Primary School (SPS) 1 of Todanan. The research data were obtained through observation and tests of critical thinking skill. Based on the observation result, student’s critical thinking skills have increased on: (1) elementary calarification by 15%; (2) basic support by 17%; (3) inference by 8%; (4) advanced clarification by 8%; (5) strategies and tactics by 11%. The result of test on critical thinking skill in cycle 1 was 62.06% of the passing grade. In cycle 2, it classically increased by 79.29%. Based on the data analysis, it was concluded that Problem Based Learning assisted with science comic book media can be used to improve the critical thinking skills of VB students of SDN 1 Todanan.